Characteristics of Pesticide Poisoning in Rural and Urban Settings in Uganda. (3rd June 2017) - Pedersen, Bastian; Ssemugabo, Charles; Nabankema, Victoria; Jørs, Erik
Pesticide poisoning is a significant burden on health care systems in many low-income countries. This study evaluates cases of registered pesticide poisonings treated in selected rural (N = 101) and urban (N = 212) health facilities in Uganda from January 2010 to August 2016. In the urban setting, pesticides were the most prevalent single poison responsible for intoxications (N = 212 [28.8%]). Self-harm constituted a significantly higher proportion of the total number of poisonings in urban (63.3%) compared with rural areas (25.6%) where unintentional poisonings prevailed. Men were older than women and represented a majority of around 60% of the cases in both the urban and rural settings. Unintentional cases were almost the only ones seen below the age of 10, whereas self-harm dominated among adolescents and young persons from 10 to 29 years of age. Organophosphorus insecticides accounted for 73.0% of the poisonings. Urban hospitals provided a more intensive treatment and had registered fever complications than rural health care settings. To minimize self-harm with pesticides, a restriction of pesticide availability as shown to be effective in other low-income countries is recommended. Training of health care workers in proper diagnosis and treatment of poisonings and improved equipment in the health care settings should be strengthened.